2008
DOI: 10.1007/s10803-007-0482-1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability and Glucagon-like peptide-2 in Children with Autism: A Controlled Pilot Study

Abstract: We measured small intestinal permeability using a lactulose:mannitol sugar permeability test in a group of children with autism, with current or previous gastrointestinal complaints. Secondly, we examined whether children with autism had an abnormal glucagon-like peptide-2 (GLP-2) response to feeding. Results were compared with sibling controls and children without developmental disabilities. We enrolled 14 children with autism, 7 developmentally normal siblings of these children and 8 healthy, developmentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
0
25
1
2
Order By: Relevance
“…Patients with autism on a reported GFCF diet had significantly lower intestinal permeability test values compared with those who were on an unrestricted diet and controls [20] . However, Robertson et al [21] did not detect any changes in intestinal permeability in a small cohort of ASD children. In another study, neither the L/M ratio nor behavioral scores were different between groups exposed to gluten/dairy or placebo.…”
Section: Gluten Sensitivity and Autismmentioning
confidence: 88%
“…Patients with autism on a reported GFCF diet had significantly lower intestinal permeability test values compared with those who were on an unrestricted diet and controls [20] . However, Robertson et al [21] did not detect any changes in intestinal permeability in a small cohort of ASD children. In another study, neither the L/M ratio nor behavioral scores were different between groups exposed to gluten/dairy or placebo.…”
Section: Gluten Sensitivity and Autismmentioning
confidence: 88%
“…Thus, although a degraded mucus barrier and less mucus-degrading bacteria seems paradoxical, A. municiphila could be a possible marker for altered mucus turnover and a thin, thus possibly more 'leaky', gut barrier (66) . However, another recent study showed no abnormal intestinal permeability in autistic children compared with healthy siblings and non-related controls (67) . The same test (a differential sugar-absorption test) was used as well as measuring glucagon-like peptide-2, an enteroendocrine molecule that is released from the GI tract in response to nutrients, which has been found to reduce intestinal permeability (68,69) .…”
Section: Abnormal Intestinal Permeabilitymentioning
confidence: 91%
“…We were interested in contrasting urinary p-cresol levels in autistic and typically developing children because ASD has been associated with enhanced frequencies of (1) excessive gut permeability, reported by at least some (D'Eufemia et al, 1996;De Magistris et al, 2010), though not all studies (Robertson et al, 2008) and (2) gut infection with cresolproducing C. difficile (Finegold et al, 2002;De Angelis et al, 2013;Keşli et al, 2014;Selmer & Andrei, 2001;Wang et al, 2011). Our initial study reported significantly elevated amounts of urinary p-cresol in 59 Italian ASD children compared with 59 age-and sex-matched controls (p50.05) (Altieri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%